2019
DOI: 10.14692/jfi.15.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Kanker Batang: Penyakit Baru pada Kopi di Lampung

Abstract: Stem Canker: A New Disease of coffee in LampungStem cancer is a new disease that has attacked smallholder coffee plantations in Lampung since 2010. The cause of the disease was unknown. This study aims to describe the symptoms of the disease, the incidence of the disease in the affected plantation, and identify morphologically and molecularly the canker pathogens of the coffee stem canker diseases. All stages of Koch’s postulate were carried out in laboratories and greenhouses. The isolated pathogens were morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Salah satu aspek penting penentu produktivitas lahan sawah tadah hujan terutama yang budidayanya dilakukan secara organik adalah ketahanan terhadap serangan hama dan penyakit (Al Viandari et al, 2022;Luo et al, 2008). Beberapa hama dan peyakit utama yang sering menyerang tanaman padi di antaranya adalah penggerek batang padi kuning (Tryporyza incertulas), wereng coklat (Nilaparvata lugens), wereng hijau (Nephotetix impicticeps), walang sangit (Leptocorisa oratorius), dan penyakit blas (Pyricularia oryzae) (Hernowo, 1995;Muis, 2007;Wiyono et al, 2014).…”
Section: Pendahuluanunclassified
“…Salah satu aspek penting penentu produktivitas lahan sawah tadah hujan terutama yang budidayanya dilakukan secara organik adalah ketahanan terhadap serangan hama dan penyakit (Al Viandari et al, 2022;Luo et al, 2008). Beberapa hama dan peyakit utama yang sering menyerang tanaman padi di antaranya adalah penggerek batang padi kuning (Tryporyza incertulas), wereng coklat (Nilaparvata lugens), wereng hijau (Nephotetix impicticeps), walang sangit (Leptocorisa oratorius), dan penyakit blas (Pyricularia oryzae) (Hernowo, 1995;Muis, 2007;Wiyono et al, 2014).…”
Section: Pendahuluanunclassified
“…Recent coffee plantations in Indonesia face coffee stem canker, a new and destructive disease caused by Fusarium solani. It was reported that severe disease infections could cause the death of coffee trees [2].…”
Section: Introductionmentioning
confidence: 99%